STUDY ON UNDERSTANDING PANCASILA VALUES AMONG TEENAGERS IN SUKA MAKMUR VILLAGE - Azahar, Ridho; Hilhamsyah Hilhamsyah; Alfi Syahri; Ade Vilya Ramadhani; Lidar Seri Harmeni Hasibuan (As-Sulthan Journal of Education, 2025)
The development of digital technology has influenced the understanding of Pancasila values, which are characteristic of the nation. The low appreciation of Pancasila values among teenagers has an impact on deviant behaviour among teenagers in society, especially in rural areas, which have different social dynamics from urban areas. Therefore, the purpose of this study is to examine the understanding of Pancasila values among teenagers. This study employs a mixed-method research approach, combining quantitative research to determine the level of teenagers' understanding and qualitative research to describe their deep understanding of the values of Pancasila. Data collection techniques include a Likert scale questionnaire for the quantitative approach and semi-structured interviews for the qualitative research. The results of the study indicate that the level of understanding of Pancasila values among teenagers is quite good, with most having a good to very good understanding of each principle. Teenagers' understanding of Pancasila is that it serves as a norm, the foundation of the state, and a guide for living in society. The ways to enhance the understanding of Pancasila values among teenagers include education through socialisation, support from various stakeholders, and formal education.